Pemanfaatan Metode Based Collaborative Filtering Untuk Rekomendasi Wisata Di Kabupaten Malang - Mufidatul Islamiyah; Puji Subekti; Titania Dwi Andini (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2019)
Tourist information in Malang district has not been widely spread on the internet, making it difficult for tourists to determine tourist destination in Malang district that will be visited. Therefore, this recommendation system was built to provide information about tourism in Malang district using the item based collaborative filtering method. The item based collaborative filtering method has the advantage of being able to increase the accuracy of the resulting object recommendations. Results from the questionnaire test that has been done, it is obtained that the tourism recommendation system is useful with the benefit level reaching 86.35% and in the item based collaborative filtering method test using the manual method in Excel and in the system produces the same predictive value namely prediction 1 with a value of 3.562, prediction 2 with a value of 3.287, and prediction 3 with a value of 1.896.